EVALUATION OF THE MICROSURGERY RESULTS FOR ACOUSTIC NEUROMA USING AN INTRAOPERATIVE NERVE MONITORING SYSTEM - Nguyễn, Thành Bắc; Vũ Văn Hòe; Đồng, Văn Hệ; Hoàng, Kim Tuấn (Tạp chí Y Dược học Quân sự (Vietnamese issues), 2023)
Objectives: To evaluate the results of microsurgery for acoustic neuroma using an intraoperative nerve monitoring system. Subjects and methods: Cross-sectional, retrospective, and prospective description of 74 patients with acoustic neuroma who were microsurgically treated in Viet Duc University Hospital from October 2016 to March 2018. Results: Women (58.11%) were more predominant than men (41.89%). The age mean was 50.41% ± 9.43 years. There was no significant difference between the tumor location on the right and left side (54.41 compared to 45.59%). There were 40 patients with large tumors (54.05%), giant tumors in 20 patients (27.02%), and 14 patients (18.92%) with small tumors < 2.5cm. Postoperative magnetic resonance examinations were indicated for 100% of patients, in which 78.37% full of tumors were taken out and 21.63% were taken almost tumors. The rate of intact facial nerve was 93.3%. The damage rate of the facial nerve was about 20.28%. The most complications were cerebral edema, bleeding, hydrocephalus, death and meningitis (5.4%; 4.05%; 4.05%; 2.7%, and 1.35%, respectively). The recovery of the function of the VII nerve, grade I, II according to House-Brackmann was 79.72%. Conclusion: Neurosurgical intervention remains the main step in the effective management of vestibular schwannomas. Using a continuous monitoring system for the facial nerve in surgery for vestibular schwannoma has reduced the rate of post-operative facial nerve paralysis.